Gadamerian Hermeneutical Analysis of Hasbi Ash-Shiddieqy's Interpretation of QS. Luqman (31):6 in the Context of Contemporary Entertainment Discourse - Fitra, Akhmad Aidil; Aboujanah, Yousuf (Al-Karim: International Journal of Quranic and Islamic Studies, 2025)
One of the challenges faced by contemporary Muslims is the relevance of classical Qur'anic interpretation in addressing modern issues. This study examines Hasbi Ash-Shiddieqy's interpretation of QS. Luqman (31):6 through the lens of Gadamerian hermeneutics, particularly in the context of contemporary entertainment discourse. The verse, often associated with prohibitions on futile speech and entertainment, has been widely debated in Islamic scholarship. This research employs a text-based qualitative method, utilizing Gadamer's philosophical hermeneutics-especially the concepts of the "fusion of horizons" and historical consciousness-for an in-depth analysis. The findings reveal that Hasbi Ash-Shiddieqy's interpretation is influenced by his historical background, including his academic training and the impact of Tafsir al-Maraghi, which shaped his pre-understanding (Vorverständnis). However, in his interpretive process, Hasbi remains committed to the primary meaning of the text, defining lahw al-hadith as anything that distracts from virtue. In contemporary contexts, this concept can extend to modern entertainment, including social media, when it leads individuals away from religious and moral values. Hasbi's approach demonstrates an effort to balance textual fidelity with contextual adaptation, offering insights into how classical interpretations can remain relevant in contemporary ethical and cultural debates. Contribution: This study contributes to the discourse on Qur'anic hermeneutics by illustrating how Gadamerian principles can help reinterpret classical exegesis to address evolving societal challenges.